Milo stover and sources of supplemental nitrogen for growing heifers - K.K. Bolsen; G. Boyett; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1975)
Seventy-two heifer calves were used in a 98-day trial to evaluate four rations: (1) forage sorghum silage plus soybean meal, (2) milo stover pellets plus soybean meal, (3) milo stover silage plus soybean meal and (4) milo stover silage plus soybean meal-corn gluten meal-urea. Daily gain was highest (P<.05) and feed required per lb. of gain lowest (P<.05) for heifers fed the forage sorghum silage ration. Heifers fed milo stover pellets consumed more feed (P<.05) than those fed any of the other three rations and, they were less efficient than those fed rations 1 or 4. The mixture of supplemental nitrogen sources fed with milo stover silage (ration 4) gave animal performance similar to that from soybean meal with milo stover silage (ration 3). The results indicate that milo stover's value is 53 to 57% that of forage sorghum in growing rations. On the average, heifers fed milo stover gained 57% as rapidly and 53% as efficiently as heifers fed forage sorghum.
Keywords: Cattlemen' s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Milo stover; Nitrogen; Heifers